A Journey to/through Family: Nostalgia, Gender, and the American Dream in Reyna Grande's The Distance Between Us. - Muñoz, Alicia; Vigil, Ariana E. (Frontiers: A Journal of Women Studies, 2019)
The article presents a literary criticism of the book "The Distance Between Us" by Reyna Grande which explores this multidimensional space through her family's experiences of separation, deprivation, and longing. It mentions importance of nostalgia in Grande's memoir is an echo of its status in Chicana/o and Latina/o cultural production. It also mentions migrant's feelings of separation or displacement from the homeland.